Meloxicam Inhibited the Proliferation of LPS-Stimulated Bovine Endometrial Epithelial Cells Through Wnt/β-Catenin and PI3K/AKT Pathways - Cui, Luying; Qu, Yang; Cai, Hele; Wang, Heng; Dong, Junsheng; Li, Jun; Qian, Chen; Li, Jianji (Frontiers in Veterinary Science, 2021)
Meloxicam is a non-steroidal anti-inflammatory drug, and has been used to relieve pain and control inflammation in cows with metritis and endometritis. Meloxicam has been found to be effective in inhibiting tissue or cell growth when it is used as an anti-inflammatory therapy. However, the influence of meloxicam on bovine endometrial regeneration has not been reported. This study was to research the effect of meloxicam (0.5 and 5 μM) on the proliferation of primary bovine endometrial epithelial cells (BEEC) stimulated by E. coli lipopolysaccharide. The cell viability, cell cycle, and cell proliferation were evaluated by Cell Counting Kit-8, flow cytometry, and cell scratch test, respectively. The mRNA transcriptions of prostaglandin-endoperoxide synthase 1 (PTGS1) and PTGS2, Toll like receptor 4, and proliferation factors were detected using quantitative reverse transcription polymerase chain reaction. The activations of phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) and Wnt/β-catenin pathways were determined using Western blot and immunofluorescence. As a result, co-treatment of meloxicam and lipopolysaccharide inhibited (P < 0.05) the cell cycle progression, and reduced (P < 0.05) the cell healing rate and the mRNA level of proliferation factors as compared the cells treated with lipopolysaccharide alone. Meloxicam decreased (P < 0.05) the lipopolysaccharide-induced PTGS2 gene expression. Neither lipopolysaccharide nor meloxicam changed PTGS1 mRNA abundance (P > 0.05). Meloxicam inhibited (P < 0.05) the lipopolysaccharide-activated Wnt/β-catenin pathway by reducing (P < 0.05) the protein levels of β-catenin, c-Myc, cyclinD1, and glycogen synthase kinase-3β, and prevented the lipopolysaccharide-induced β-catenin from entering the nucleus. Meloxicam suppressed (P < 0.05) the phosphorylation of PI3K and AKT. In conclusion, meloxicam alone did not influence the cell cycle progression or the cell proliferation in BEEC, but caused cell cycle arrest and inhibited cell proliferation in lipopolysaccharide-stimulated BEEC. This inhibitory effect of meloxicam was probably mediated by Wnt/β-catenin and PI3K/AKT pathways.